Processing of It and This in Written Narrative Discourse. Issue 3 (3rd April 2018) - Çokal, Derya; Sturt, Patrick; Ferreira, Fernanda
Abstract : Two experiments explored the hypothesis that anaphors and demonstratives signal different procedural instructions: Whereas the anaphor it brings a concrete entity into a reader's focus, the demonstrative this directs the focus to a predicate proposition in a discourse representation. The findings from an online eye-tracking reading experiment confirm that preferences for it and this differ as predicted. Moreover, a sentence-completion experiment revealed converging evidence for this difference, with clear differences in antecedent preferences for it and this . Overall, findings show that the processing and use of anaphoric expressions is affected by the interaction between the lexical characteristics of referential forms and different types of referent.